Targeting the NLRP3 Inflammasome in Severe COVID-19 - Freeman, Tracey L.; Swartz, Talia H. (Frontiers in Immunology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a member of the genus Betacoronavirus within the family Coronaviridae. It is an enveloped single-stranded positive-sense RNA virus. Since December of 2019, a global expansion of the infection has occurred with widespread dissemination of coronavirus disease 2019 (COVID-19). COVID-19 often manifests as only mild cold-like symptomatology, but severe disease with complications occurs in 15% of cases. Respiratory failure occurs in severe disease that can be accompanied by a systemic inflammatory reaction characterized by inflammatory cytokine release. In severe cases, fatality is caused by the rapid development of severe lung injury characteristic of acute respiratory distress syndrome (ARDS). Although ARDS is a complication of SARS-CoV-2 infection, it is not viral replication or infection that causes tissue injury; rather, it is the result of dysregulated hyperinflammation in response to viral infection. This pathology is characterized by intense, rapid stimulation of the innate immune response that triggers activation of the Nod-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome pathway and release of its products including the proinflammatory cytokines IL-6 and IL-1β. Here we review the literature that describes the pathogenesis of severe COVID-19 and NLRP3 activation and describe an important role in targeting this pathway for the treatment of severe COVID-19.